1999
DOI: 10.1007/s002109900124
|View full text |Cite
|
Sign up to set email alerts
|

On the contractile function of protein phosphatases in isolated human coronary arteries

Abstract: It is unknown whether protein phosphatases types 1 and 2A are present in and can regulate the tone of human vascular tissue. The expression and possible function of serine/threonine protein phosphatases (PP) type 1 (PP1) and type 2A (PP2A) were studied in isolated human coronary arteries. Catalytic subunits of PPI and PP2A were identified by means of phosphatase activity measurement in tissue homogenates, by separation of enriched extracts through affinity column chromatography, by immunoblotting with specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Our current data confirm and extend our previous data that phosphatase inhibition may be a potential treatment modality for heart failure. However, as we have shown in previous studies, cantharidin induces vasoconstriction in isolated animal coronary muscle strips (Knapp et al 1997;Knapp et al 1998a, b) and human coronary muscle strips (Knapp et al 1999). Hence, cantharidin in humans would increase the force of contraction in the cardiac muscles; however, cantharidin would simultaneously reduce or even stop coronary perfusion.…”
Section: Clinical Relevancesupporting
confidence: 49%
“…Our current data confirm and extend our previous data that phosphatase inhibition may be a potential treatment modality for heart failure. However, as we have shown in previous studies, cantharidin induces vasoconstriction in isolated animal coronary muscle strips (Knapp et al 1997;Knapp et al 1998a, b) and human coronary muscle strips (Knapp et al 1999). Hence, cantharidin in humans would increase the force of contraction in the cardiac muscles; however, cantharidin would simultaneously reduce or even stop coronary perfusion.…”
Section: Clinical Relevancesupporting
confidence: 49%
“…We were interested in not only how they alter the signals leading from the sarcolemmal receptors to the activation of protein kinases but also how they might play a role in the development of cardiac hypertrophy (Boknik et al, 2000) and even heart failure, which we looked at in some initial studies in human hearts (Neumann et al, 1999). In this line, we quite extensively characterized PP2A in humans (Knapp et al, 1999) and animal hearts (Neumann et al, 1993;Gombosova et al, 1998), overexpressed the catalytic subunit of PP2A (Gergs et al, 2004), and studied its role under stressful conditions, such as hypertension-induced hypertrophy (aortic banding) myocardial infarction (Brüchert et al, 2008;Grote-Wessels et al, 2008;Hoehn et al, 2015). Because the H 2 -histamine receptor mediates its effects via cAMP and protein kinase A and phospholamban phosphorylation (Gergs et al, 2019), it seemed logical to test the influence of PP2A on H 2 -histamine receptor-mediated effects because PP2A is known to dephosphorylate phospholamban not only in vitro (Neumann et al, 1993) but also in the beating heart (Gergs et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Such a drug is in principle available with okadaic acid: at 10 nM, it inhibits only PP2A not PP1 [4]. Regrettably, its action is not restricted to the myocardium, and we have shown that, by inhibition of smooth muscle phosphatases, it leads to vasoconstriction in isolated human coronary arteries which would worsen cardiac function [57]. We speculate here that the search for cardiac muscle specific inhibitors of PP2A might be reasonable for the pharmacological treatment of the aging human heart.…”
Section: Discussionmentioning
confidence: 99%